Pulmonary arterial hypertension: tailoring treatment to risk in the current era. (20th December 2017) - Gaine, Sean; McLaughlin, Vallerie
Recent advances in the treatment of pulmonary arterial hypertension (PAH) have led to improved patient outcomes. Multiple PAH therapies are now available and optimising the use of these drugs in clinical practice is vital. In this review, we discuss the management of PAH patients in the context of current treatment guidelines and supporting clinical evidence. In clinical practice, considerable emphasis is placed on the importance of making treatment decisions guided by each patient's risk status, which should be assessed using multiple prognostic parameters. As PAH is a progressive disease, regular assessments are essential to ensure that any change in risk is detected in a timely manner and treatment is adjusted accordingly. With the availability of therapies that target three different pathogenic pathways, combination therapy is now the standard of care. For most patients, this involves dual combination therapy with agents targeting the endothelin and nitric oxide pathways. Therapies targeting the prostacyclin pathway should be added for patients receiving dual combination therapy who do not achieve a low-risk status. There is also a need for a holistic approach to treatment beyond pharmacological therapies. Implementation of all these approaches will ensure that PAH patients receive maximal benefit from currently available therapies. Optimal PAH treatment requires frequent multiparameter risk assessment and early initiation of combination therapy http://ow.ly/IA6t30fPceT